Ageing and Skills: The Case of Literacy Skills - Garry F. Barrett; W. Craig Riddell (Institute of Labor Economics (IZA), 2019)
The relationship between ageing and skills is of growing policy significance due to population ageing, the changing nature of work and the importance of literacy for social and economic well-being. This article examines the relationship between age and literacy skills in a sample of OECD countries using three internationally comparable surveys. By pooling the survey data across time we can separate birth cohort and ageing effects. In doing so we find literacy skills decline with age and that, in most of our sample countries, successive birth cohorts tend to have poorer literacy outcomes. Therefore, once we control for cohort effects the rate at which literacy proficiency falls with age is much more pronounced than that which is apparent based on the cross-sectional relationship between age and literacy skills at a point in time. Further, in studying the literacy-age relationship across the skill distribution in Canada we find a more pronounced decline in literacy skills with age at lower percentiles, which suggests that higher initial literacy moderates the influence of cognitive ageing.
Keywords: I20; J14; J24; 330; human capital; ageing; cognitive skills; literacy; cohort effects